Hevelius - Siemiginowska, Anna.; Forkiewicz, Jan ( -2015).; Muzeum Historii Miasta Gdańska (Gdańsk : Muzeum Historii Miasta Gdańska, 1987)
Druk.
Keywords: Heweliusz, Jan -- (1611-1687); Heweliusz, Jan -- (1611-1687) -- rocznice -- druki ulotne